Serum leptin levels in poultry - Osorio, José Henry (2019)
The aim of this study was to determine the levels of leptin in broilers and laying hens by using a kit designed for human samples. Fasting blood samples were collected from 80 broilers of the Cobb 500 line of 4 weeks of age (40 females and 40 males) and 86 hens of 26 weeks of age (43 Lohmann Brown and 43 Hy-line). Leptin levels were determined by an ELISA sandwich, after validation of the kit for use in commercial poultry. The mean, minimum, maximum and standard deviation values ​​of leptin for broilers were 0.61, 0.12, 3.99 and 0.10 ng/ml, respectively, without significant difference between sexes. Laying hens reported a mean, minimum, maximum and standard deviation values ​​of 0.66, 0.16, 1.83 and 0.11 ng/ml, respectively, without significant difference between lines. Similarly, no statistical difference was found between broiler chickens and laying hens. The results of the study indicate that the reference values for leptin in chickens and chickens are 0.63 ng/ml, and the levels can be measured by using the human kit.